Anti-inflammatory activity of Urera baccifera (Urticaceae) in Sprague-Dawley rats - Beatriz Badilla; Gerardo Mora; Antonio José Lapa; Jose Arthur Silva Emim (Revista de Biología Tropical, 1999)
On a preliminary test, anti-inflammatory and analgesic dose-related activities on rats were observed for the aqueous fraction of Urera baccifera; this extract was bioassay-guided fractionated and the final aqueous fraction was used according the ethnobotanical use. Carrageenan-induced edema (n=6), was used as an assay in the fractionating process. The anti-inflammatory and antinociceptive properties of the final aqueous fraction were studied using in vivo models. For the anti-inflammatory activity rat paw edema (n=6), pleurisy induced by carrageenan (n=6) and ear edema induced by topical croton oil (n=6) models were used, and tail-flick test (n=6), abdominal constrictions induced by acetic acid (n=6), and formalin test (n=6), were used for the antinociceptive activity. The tests performed showed an inhibition effect on leukocyte migration, and a reduction on pleural exudate, as well as dose-dependant peripheral analgesic activity, at a range of 25-100 mg/kg i.p. The final aqueous fraction contains most of the anti-inflammatory activity of the plant U. baccifera. A possible mechanism of action is discussed and based on the results we conclude that this plant has a potential for both anti-inflammatory and analgesic activity at the clinical level.